Low-temperature kinetics and dynamics with Coulomb crystals. - Heazlewood, B; Softley, T (2015)
Coulomb crystals-as a source of translationally cold, highly localized ions-are being increasingly utilized in the investigation of ion-molecule reaction dynamics in the cold regime. To develop a fundamental understanding of ion-molecule reactions, and to challenge existing models that describe the rates, product branching ratios, and temperature dependence of such processes, investigators need to exercise full control over the experimental reaction parameters. This requires not only state selection of the reactants, but also control over the collision process (e.g., the collisional energy and angular momentum) and state-selective product detection. The combination of Coulomb crystals in ion traps with cold neutral-molecule sources is enabling the measurement of state-selective reaction rates in a diverse range of systems. With the development of appropriate product detection techniques, we are moving toward the ultimate goal of examining low-energy, state-to-state ion-molecule reaction dynamics.